Can Simulation Based-Team Training Impact Bedside Teamwork in a Pediatric Intensive Care Unit? - Colman, Nora; Figueroa, Janet; McCracken, Courtney; Hebbar, Kiran B. (Journal of Pediatric Intensive Care, 2019)
Effective teamwork performance is essential to the delivery of high-quality and safe patient care. In this mixed methodological observational cohort study, we evaluated team performance immediately following a real medical crisis in a pediatric intensive care unit (PICU) following implementation of a simulation-based team training (SBTT) program. Comparison of teamwork skills when rated by study observers demonstrated a statistically significant improvement in 12 out of 15 composite teamwork skills during real emergency events following SBTT (p < 0.05). Pre- and post-SBTT intervention survey data demonstrated an improvement in the perception of teamwork, most notable in the area of shared mental model and situational awareness following SBTT. Study results suggest that teamwork behaviors and skills acquired during SBTT can translate into improved bedside performance in the PICU.
Keywords: simulation; pediatric; team performance; teamwork; cardiac arrest; pediatric intensive care